Brève histoire de la paroisse des Saints-Anges, 1676-2001 - Robichaud, André; Lamarche, Hélène; Dumont-Frenette, Geneviève (Société d'histoire de Lachine, 2001)
Keywords: Lachine

Étude historique du développement urbain. L’axe du canal de Lachine – partie Lachine et LaSalle - Poitras, Claire; Aubry, Jean-Christian (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2004)
Keywords: Lachine (canal)

History's Floodgate: The Lachine Canal Reopens - Gedeon, Julie (The Beaver, 2002)
Keywords: Lachine (canal)

Behind the Scene of the Lachine Canal Landscape - Desloges, Yvon (The Journal of the Society for Industrial Archeology, 2003)
Keywords: Lachine (canal)

Le canal de Lachine: les métamorphoses d’un quartier - Bélisle, Jean (Continuité, 2003)
Keywords: Lachine (canal)

Le canal de Lachine: l’eau à l’œuvre - Desloges, Yvon (Continuité, 2002)
Keywords: Lachine (canal)

Moments d’histoire à Lachine - Buteau, Hélène (Continuité, 2001)
Keywords: Archéologie; Lachine

L'organisation spatiale du corridor du canal de Lachine au XIXe siècle - Desjardins, Pauline (Association des archéologues du Québec, 2006)
Keywords: Lachine (canal)

Understanding the Built Form of Industrialization along the Lachine Canal in Montreal - Bliek, Desmond; Gauthier, Pierre (Urban History Review / Revue d'histoire urbaine, 2006)
Keywords: Lachine (canal)

Étude historique du développement urbain. L’axe du canal de Lachine – partie Sud-Ouest - Poitras, Claire; Bérubé, Harold (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2004)
Keywords: Lachine (canal)

L’émeute de Lachine en 1812: la coordination d’une contestation populaire - Dessureault, Christian (Revue d'histoire de l'Amérique française, 2008)
Keywords: Lachine; Émeutes

Daly et Morin, à la recherche du patrimoine industriel de Lachine - Avon, Hélène (Université de Sherbrooke, 2003)
Keywords: Lachine; Patrimoine

From Meritocracy to Seniority: Shifting Masculine Aesthetics Among blue-collar workers in Montréal Lachine - Desforges, Exan Yuen (Université Concordia, 2008)
Keywords: Lachine; Quartiers

French Canadians and the Beginning of the War of 1812: Revisiting the Lachine Riot - Mills, Sean (Histoire sociale / Social History, 2005)
Historians have generally claimed that, during the War of 1812, unlike in earlier periods, French Canadians eagerly rallied to the British cause and willingly fought to defend British North America from American invasion. Nearly all studies of French-Canadian participation in the war, however, focus on the Battle of Châteauguay in 1813, and few examine the first year of the war. A close look at French Canadians’ reactions to the outbreak of the War of 1812 would indicate that they were hardly unanimous in their support. A detailed study of the largest and most violent act of resistance — a riot that broke out at Lachine at the beginning of July 1812 — reveals some of the reasons why so many habitants refused to perform their militia duty.
Keywords: Guerre; Lachine; Émeutes

Évaluation du patrimoine urbain: arrondissement de Lachine - Service de la mise en valeur du territoire et du patrimoine (Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Lachine; Patrimoine

The Lachine Canal: Riding the Waves of Industrial and Urban Development, 1860-1950 - Desloges, Yvon; Gelly, Alain (Septentrion, 2002)
Keywords: Lachine (canal); Énergie hydraulique

Le canal de Lachine: du tumulte des flots à l'essor industriel et urbain, 1860-1950 - Desloges, Yvon; Gelly, Alain (Septentrion, 2002)
Keywords: Lachine (canal); Énergie hydraulique

A Precipitous Decline, Steam as a Motive Power in Montreal : A Case Study of the Lachine Canal Industries - Gelly, Alain (The Journal of the Society for Industrial Archeology, 2003)
Keywords: Lachine (canal); Énergie hydraulique

Marriage index: Saint Andrew's Presbyterian Church, Lachine, 1818-1925 - Dunn, Robert (Quebec Family History Society, 2006)
Keywords: Lachine; Mariage; Presbytériens; Protestants; Registres

Un essor laborieux : l'électricité et le monde industriel. Les choix énergétiques des entrepises du canal de Lachine, Montréal, 1880-1920 - Gelly, Alain (Les territoires de l’entreprise / The Territories of Business, 2004)
Keywords: Lachine (canal); Électricité; Énergie hydraulique

The Pictured and the Posed: Nineteenth Century Touristic Images of the Lachine Rapids - Eagan, Mireille M. (Université Concordia, 2008)
Keywords: Lachine; Paysages; Peinture; Photographie; Tourisme

Autour de l'enseigne Five Roses: la minoterie Ogilvie, figure de proue du canal de Lachine - Cadorette, Paul-Émile (Bulletin de l'Association québécoise pour le patrimoine industriel, 2006)
Keywords: Alimentation; Lachine (canal); Meunerie; Ogilvie Flour Mills

Enjeux de redéveloppement et morphologie urbaine aux abords du canal de Lachine: Petite-Bourgogne et Pointe-Sainte-Charles - Gildas, Michel (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2000)
Keywords: Lachine (canal); Petite-Bourgogne; Pointe-Saint-Charles; Quartiers

D'audace en mémoire: le lieu dit Lachine, un regard archéologique - Buteau, Hélène; Chevrier, Daniel (In Situ, 2001)
Keywords: Lachine; Le Ber, Jacques; Le Moyne de Longueuil, Charles; Maison LeBer-LeMoyne

Brève histoire de la paroisse des Saints-Anges, 1676-2008 - Robichaud, André; Lamarche, Hélène; Dumont-Frenette, Geneviève (Société d'histoire de Lachine, 2008)
Keywords: Lachine

Essai de synthèse ethnohistorique du secteur des Rapides de Lachine. Rapport final - Des Roches, Jacques (Communauté urbaine de Montréal, Service de la mise en valeur du territoire, Division de l'aménagement, 2001)

Transportons-nous, jadis! Une petite histoire du transport (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2006)
Keywords: Automobile; Lachine (canal); Navigation; Ponts; Tramways; Transport en commun

Mouvement syndical et mobilisation pour l’emploi: renouvellement des enjeux et des modalités d’action - Fontan, Jean-Marc; Klein, Juan-Luis (Politique et sociétés, 2000)
Keywords: Confédération des syndicats nationaux; Dominion Bridge; Fédération des travailleurs et travailleuses du Québec (FTQ); Lachine

Programme d'inventaire archéologique de la Pointe-des-Seigneurs - Société d'archéomatique Chronogramme-Lauverbec (Société d'archéomatique Chronogramme-Lauverbec, 2002)
Keywords: Artisans; Confection; Fer et acier; Lachine (canal); Meunerie; Mouleurs; Ogilvie Flour Mills; Énergie hydraulique

Montréal au fil du temps - McQuarrie, John; Demers, Jacques (Magic Light Publishing, 2002)
Keywords: Hôtel de ville; Jardin botanique; Lachine (canal); Mont Royal; Places publiques; Pointe-à-Callière; Rues; Squares; Églises